A Numerical Evidence of Biosonar Beam Formation of a Neonate Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Wei, Chong; Song, Zhongchang; Au, Whitlow WL; Zhang, Yu; Wang, Ding (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
Yangtze finless porpoises (Neophocaena asiaeorientalis) are known to use the narrowband signals for echolocation. In this study, a finite-element model was configured based on computed tomography imaging technique and tissue physical properties measurement to simulate biosonar signal emission and transmission processes through animal’s head. The roles of the main structures in the head such as the air sacs, melon, bony structures, connective tissue, blubber, mandibular fat on the biosonar beam formation were investigated, and the relative importance of these structures was compared. The biosonar beam properties of this neonate porpoise were compared with those of adult ones. The method in this paper suggested an effective way for investigating the acoustic processes in the heads of the neonate odontocetes.